Pengaruh,Komunikasi Kerja,Budaya Organisasi, Dan Kerjasama Tim Terhadap Kinerja Karyawan (Studi Pada Rocket Chicken Cabang Semarang Barat) - Mahendra, Riskhi Rudi; Rozak, Hasan Abdul (JURNAL ILMIAH EDUNOMIKA, 2024)
This study's goal is to determine and investigate the effects that corporate culture, work communication, and teamwork have on employees' performance. The research was done at the Rocket Chicken location in West Semarang. 88 respondents who worked in Rocket Chicken's service department made up the study's sample population, and they were chosen using the census method. The technique used to collect statistical information for this study was a questionnaire. Among the methods tolerant of to analyze the data in the interim are validity tests, reliability tests, multiple linear regression tests, T tests, F tests, and determination coefficient tests (R2) with the SPSS 29 application. Keywords : Work Communicatin ,Organizational Culture, and Teamwork On Employe Performance